2021
DOI: 10.1021/acsami.1c09378
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Synthesis Conditions in Na-Rich Prussian Blue Analogues

Abstract: Sodium-rich iron hexacyanoferrates were prepared by coprecipitation, hydrothermal route, and under reflux, with or without dehydration. They were obtained with different structures described in cubic, orthorhombic, or rhombohedral symmetry, with variable compositions in sodium, water, and cationic vacancies and with a variety of morphologies. This series of sodium-rich Prussian blue analogues allowed addressing the relationship between synthesis conditions, composition, structure, morphology, and electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…In recent years, with the rapid development of a new energy industry, energy-saving, resource-rich, and environment-friendly energy storage devices are the necessary conditions for the sustainable development of modern human society. Lithium-ion batteries (LIBs) have been increasingly applied in portable electronic products and electric vehicles due to their excellent performance, which makes it difficult for the Earth’s limited lithium resources to meet the needs of the explosive growth of the energy storage market . Therefore, people have begun to focus on sodium-ion batteries (SIBs).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of a new energy industry, energy-saving, resource-rich, and environment-friendly energy storage devices are the necessary conditions for the sustainable development of modern human society. Lithium-ion batteries (LIBs) have been increasingly applied in portable electronic products and electric vehicles due to their excellent performance, which makes it difficult for the Earth’s limited lithium resources to meet the needs of the explosive growth of the energy storage market . Therefore, people have begun to focus on sodium-ion batteries (SIBs).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically for PW, there are inconsistencies regarding the structure of the hydrated phase. For example, Camacho et al reported a rhombohedral R 3 structure for Na 1.86 Fe[Fe(CN) 6 ]•1.92H 2 O with oxygen positioned on half of the faces of the subcube [13]. This paper also reported a new orthorhombic Na-rich PBA (Na 1.8 Fe[Fe(CN) 6 ]•0.7H 2 O) [13].…”
Section: Introductionmentioning
confidence: 61%
“…For example, Camacho et al reported a rhombohedral R 3 structure for Na 1.86 Fe[Fe(CN) 6 ]•1.92H 2 O with oxygen positioned on half of the faces of the subcube [13]. This paper also reported a new orthorhombic Na-rich PBA (Na 1.8 Fe[Fe(CN) 6 ]•0.7H 2 O) [13]. On the other hand, Rudola et al reported a monoclinic P2 1 /n structure for Na 2 Fe[Fe(CN) 6 ]•2H 2 O with only a single oxygen atom at the face of the subcube [7].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, some XRD peaks of the lattice, such as (220) and (420) diffraction, split into a double peak structure, manifesting a rhombohedral PBA structure, which may be due to the high concentration of sodium ions in the PW-H lattice. 28,31,32 In comparison with the traditional washing method with water, the Na-enriched framework can be obtained with sodium ascorbate aqueous solution as the washing agent, and it is non-toxic, is obtained in high yield and is applicable for large scale production. The specific surface area of PW-H is 32.5 m 2 g −1 , which is larger than that of PW-L (15.0 m 2 g −1 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%